Morphological and molecular analyses of larval and adult stages of Echinoparyphium recurvatum von Linstow 1873 (Digenea: Echinostomatidae) from central Mexico. Issue 4 (July 2015) - Sereno-Uribe, A.L.; Pinacho-Pinacho, C.D.; Sanchéz Cordero, V.; García-Varela, M.
Abstract In central Mexico, populations of the freshwater snail Physella cubensis were infected with metacercariae from a species of Echinoparyphium (Digenea: Echinostomatidae). In the current study, we describe both larval and adult stages of this species obtained from experimental and natural infections. A total 180 snails were collected from Patzcuaro Lake, Michoacan state in central Mexico in July 2012. In the laboratory snails were placed in individual vials and exposed to light with the aim of observing emergence of cercariae. To obtain metacercariae, uninfected snails (P. cubensis) were exposed to cercariae. Chicks were infected with metacercariae to obtain adults. Nine days post-infection, eggs were recovered and incubated in tap water at room temperature to observe miracidia. Adults obtained from natural and experimentally infected hosts possess a head collar with 45 spines in two alternating rows, confirming the identification as Echinoparyphium recurvatum von Linstow 1873. To test the conspecificity of all stages, sequences of nuclear internal transcribed spacer 1 (ITS1), 5.8S and ITS2 rDNA were obtained from two adult worms recovered from chicks and also a natural avian host, the shoveler duck Anas clypeata, together with five cercarial and four metacercarial isolates from nine snails. The genetic divergence estimated among the 13 isolates was very low, ranging from 0 to 0.6%. Phylogenetic analyses inferred by maximum likelihood and Bayesian methods showed that all isolates of E. recurvatum form a single clade with strong support. The presence of E. recurvatum in P. cubensis and A. clypeata from central Mexico represents new host reports, and extends the distribution range in the Americas.